Optimizing the Mechanical Properties and Corrosion Performance of Low-Alloyed Mg-Zn-Ca Alloy by Regulating Zn/Ca Atomic Ratios - Yuan Jin; Shaoyuan Lyu; Qianqian Yu; Minfang Chen (Solids, 2025)
The microstructural, mechanical and corrosion properties of low-alloyed Mg-Zn-Ca alloys with different Zn/Ca atomic ratios were investigated. The results show that the microstructure of the extruded Mg-1Zn-0.3Ca (ZX1.0) alloy mainly consists of α-Mg and Ca2Mg6Zn3 phases and a small amount of Mg2Ca phase. In contrast, the Mg2Ca phase disappears in the alloys Mg-1.4Zn-0.3Ca (ZX1.4), Mg-1.8Zn-0.3Ca (ZX1.8) and Mg-2.3Zn-0.5Ca (ZX2.3). The Ca2Mg6Zn3 phases are mainly distributed along the extrusion direction, showing irregular particle shapes and banded particles. Meanwhile, the grain size of the extruded Mg-Zn-Ca alloy is reduced gradually with the increase of the Zn and Ca contents, decreasing from 1.87 μm in ZX1.0 to 1.28 μm in ZX2.3 alloy. Fine grain strengthening and second-phase strengthening increase the yield strength and ultimate tensile strength of the alloy. In addition, when the Zn/Ca ratio is the same, the total elemental content dominates the effect on alloy properties. When increasing the Zn/Ca ratio, the potential difference between Ca2Mg6Zn3 and the Mg matrix increased, resulting in an increase in galvanic corrosion. The negative effect of the volume fraction of the second phase and the positive effect of the fine grain size determine the corrosion performance together. Therefore, ZX1.8 exhibits the best corrosion resistance, of 0.14 mm/y.